strategy analysis in the face of new normal conditions to maintain human resource performance ( case study: regency government and state-owned enterprises) - Agung Subeno; Siti Musyaroh; Septi Ariyani; Nuning Nur Aini; Sapto Supriyanto (Institute of Computer Science (IOCS), 2021)
The new normal era began to be imposed by the government with the Decree of the Minister of Health No. HK.01.07/Menkes/382/2020 on Health Protocols for People in Public Places and Facilities to Prevent and Control Corona Virus Disease 2019 (Covid-19) set on June 19, 2020. Objects used as studies in research at the Demak And Some District Governments BUMN (Badan Usaha Milik Negara) The purpose of this research is to know and understand the strategy of national private companies to improve their performance employees in the face of the new normal. The research process is used by collecting libraries from journals, books and information from website pages. The analysis produced a description that adjustment of the ASN Work System enters work and comply with the provisions of applicable working hours. At the same time, state-owned enterprises establish health protocols according to regulations and conduct activities according to the relevant law.